Expression of podocalyxin-like protein is an independent prognostic biomarker in resected esophageal and gastric adenocarcinoma. Issue 1 (December 2016) - Borg, David; Hedner, Charlotta; Nodin, Björn; Larsson, Anna; Johnsson, Anders; Eberhard, Jakob; Jirström, Karin
Abstract Background Podocalyxin-like protein (PODXL) is a cell surface transmembrane glycoprotein, the expression of which has been associated with poor prognosis in a range of malignancies. The aim of this study was to investigate the impact of PODXL expression on survival in esophageal and gastric adenocarcinoma. Methods The study cohort consists of a consecutive series of 174 patients with esophageal (including the gastroesophageal junction) or gastric adenocarcinoma, surgically treated between 2006 and 2010 and not subjected to neoadjuvant treatment. Immunohistochemical expression of PODXL was assessed in tissue microarrays with cores from primary tumors, lymph node metastases, intestinal metaplasia and adjacent normal epithelium. Survival analyses were performed on patients with no distant metastases and no macroscopic residual tumor. Results In the majority of cases, expression of PODXL was significantly higher in cancer cells compared to normal epithelial cells and was significantly associated with lymph node metastases and high grade tumors. In esophageal adenocarcinoma, Kaplan-Meier analyses revealed that patients with PODXL negative tumors had a superior time to recurrence (TTR) and overall survival (OS) compared to patients with PODXL positive tumors. In gastric adenocarcinoma, patients with PODXL negative tumors had a superior TTR and a trend towards an improved OS. In esophageal and gastric adenocarcinoma combined, the prognostic significance of PODXL expression on TTR was confirmed in unadjusted Cox regression analysis (HR = 5.36, 95 % CI 1.68-17.06, p  = 0.005) and remained significant in the adjusted model (HR = 3.39, 95 % CI 1.01-11.35, p  = 0.048). Moreover, the impact of PODXL expression on OS was also confirmed in unadjusted analysis (HR = 2.52, 95 % CI 1.31-4.85, p  = 0.006) and remained significant in the adjusted model (HR = 2.03, 95 % CI 1.04-3.98, p  = 0.039). Conclusions In esophageal and gastric adenocarcinoma, PODXL expression is an independent prognostic biomarker for reduced time to recurrence and poor overall survival. This is the first report on the prognostic role of PODXL in esophageal adenocarcinoma and validates recent findings in gastric cancer.